1998
DOI: 10.1007/s002449900415
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Mass Budget for Mercury in the Everglades Nutrient Removal Project

Abstract: The Everglades Nutrient Removal Project (ENRP) is a 1,545-ha prototype wetland constructed to test a larger system of stormwater-treatment areas that is being used to remove agricultural nutrients and help restore the remnant Everglades. Concerns that the ENRP may lead to mercury bioaccumulation as observed in other newly created reservoirs resulted in an effort to construct a mercury mass budget and measure bioaccumulation in aquatic organisms. For the first 2 years of operation, total mercury (THg) and methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The U.S. Environmental Protection Agency (USEPA) had encountered only two slightly higher MeHg values in 100s of samples of surface water collected in South Florida from 1995-1999 (D. Scheidt, USEPA, personal communication). Further, 4.8 ng MeHg/L represented 83% of the 5.8 ng THg/L present in the paired sample and this %MeHg was elevated relative to other areas (Southworth et al, 2002) and even relative to high values typically found in the Everglades Miles and Fink, 1998). MeHg concentration in the adjacent Cell 2 was only 10% of that detected in Cell 1 (Figure 3).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The U.S. Environmental Protection Agency (USEPA) had encountered only two slightly higher MeHg values in 100s of samples of surface water collected in South Florida from 1995-1999 (D. Scheidt, USEPA, personal communication). Further, 4.8 ng MeHg/L represented 83% of the 5.8 ng THg/L present in the paired sample and this %MeHg was elevated relative to other areas (Southworth et al, 2002) and even relative to high values typically found in the Everglades Miles and Fink, 1998). MeHg concentration in the adjacent Cell 2 was only 10% of that detected in Cell 1 (Figure 3).…”
Section: Resultsmentioning
confidence: 85%
“…Although studies elsewhere continued to report both "first flush" of inorganic mercury and MeHg biomagnification leading to a so-called "reservoir effect" (Kelly et al, 1997;Paterson et al, 1998;Bodaly and Fudge, 1999), results from monitoring the prototype STA, the Everglades Nutrient Removal (ENR) Project, found no evidence of these problems (Watras, 1994;Miles and Fink, 1998). Quite the opposite, the ENR Project was found to be a net sink for both total mercury (THg) as well as MeHg.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Reported Hg concentrations in the large fish trophic group ranged from 0.030 to 0.056 ppm Hg in bluegill in WCA 1 (Miles and Fink, 1998) to 1.7-1.8 ppm Hg in largemouth bass in Shark Slough (Loftus and Bass, 1992). Concentrations as high as 7 ppm have been reported in large predatory fish in the Everglades (Stober et al, 1995).…”
Section: Mercury Risks To Everglades Wildlifementioning
confidence: 98%
“…Because of the high levels of Hg found in largemouth bass and other freshwater gamefish, fish consumption advisories have been issued for the state of Florida (Ware et al, 1990). Also, alligator (Alligtor mississippiensis) hunting in the Everglades was restricted because of elevated levels of Hg (Loftus and Bass, 1992), and the Florida Department of Environmental Protection criterion for total Hg in freshwater (12 ng/L; class III water) has been exceeded in the Everglades (Miles and Fink, 1998). The bioaccumulation of Hg in the aquatic food web has also been associated with health problems in top predators of the Everglades (Frederick and Spalding, 1994;Roelke et al, 1991).…”
Section: Introductionmentioning
confidence: 99%